Implementation Of Central Language Movement As A Habit Of Arabic Language Learning To Improve The Activeness Students Of SMP Muhammadiyah 4 Giri Gresik - Wahyu adi Nugroho; Noor Amirudin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Arabic language learning at the junior high school level still faces the problem of low student engagement due to the dominance of conventional learning methods that focus on memorization and translation. The teacher-centered learning approach limits student engagement in the communicative use of Arabic, resulting in boredom, low self-confidence, and affective barriers to speaking skills. This situation encourages the implementation of more innovative, communicative, and contextual learning strategies. The Central Language Movement (CLM) is a language learning approach rooted in the principles of Community Language Learning and language immersion, emphasizing the habituation of Arabic language use through natural interactions within the classroom community. This study aims to analyze the application of CLM as a strategy for habituating Arabic language learning to increase the engagement of eighth-grade students at Muhammadiyah 4 Giri Junior High School. This study used a descriptive qualitative approach with a case study design. Data collection was conducted through semi-structured interviews with teachers and students, participant observation during the learning process, and supporting documentation. Research subjects were selected using a purposive sampling technique. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. Data validity was maintained through source and method triangulation, member checking, and an audit trail. The results showed that before the implementation of CLM, student engagement was relatively low, especially in speaking skills. After consistent implementation of CLM, students demonstrated increased engagement, confidence, and courage in using Arabic in simple spoken interactions. CLM implementation also reduced language anxiety and created a communicative and humanistic learning environment. Therefore, CLM is an effective, applicable, and relevant Arabic language learning model for junior high school students, including those with limited learning resources.